Becoming Sustainable, The New Frontier in Soft Robotics. Issue 19 (18th December 2020) - Hartmann, Florian; Baumgartner, Melanie; Kaltenbrunner, Martin
Abstract: The advancement of technology has a profound and far‐reaching impact on the society, now penetrating all areas of life. From cradle to grave, one is supported by and depends on a wide range of electronic and robotic appliances, with an ever more intimate integration of the digital and biological spheres. These advances, however, often come at the price of negatively impacting our ecosystem, with growing demands on energy, contributions to greenhouse gas emissions and environmental pollution—from production to improper disposal. Mitigating these adverse effects is among the grand challenges of the society and at the forefront of materials research. The currently emerging forms of soft, biologically inspired electronics and robotics have the unique potential of becoming not only like their natural antitypes in performance and capabilities, but also in terms of their ecological footprint. This review outlines the rise of sustainable materials in soft and bioinspired robotics, targeting all robotic components from actuators to energy storage and electronics. The state‐of‐the‐art in biobased robotics spans flourishing fields and applications ranging from microbots operating in vivo to biohybrid machines and fully biodegradable yet resilient actuators. These first steps initiate the evolution of robotics and guide them into a sustainable future. Abstract : In future, robots will be seamlessly integrated in everyday life and—as much as consumer electronics is omnipresent today—assist in a myriad of tasks. However, environmental concerns at their end‐of‐life phase necessitate sustainable solutions for actuators, energy storage, electronics, and all involved materials. Soft and bioinspired robotics offer a remarkably unique potential to succeed this challenge.